Thermal and barrier properties of EVOH/EFG nanocomposite films for packaging applications: Effect of the mixing method. Issue 6 (29th December 2014) - Kwon, Hyok; Kim, Dowan; Seo, Jongchul
Abstract : Ethylene‐vinyl alcohol copolymer (EVOH)/exfoliated graphite (EFG) nanocomposite films were prepared by precoating EFG on the EVOH surface and conducting a successive melt‐extrusion process. Their physical properties were strongly dependent on the EFG content and the mixing method, which strongly affected the morphology and surface properties of the nanocomposite films. The hydrophobicity and water resistance property of EVOH increased by incorporating hydrophobic EFG and their effects were more pronounced in the precoating method, which is related to good dispersion of EFG in EVOH and an enhanced crystalline structure. The incorporation of EFG into EVOH by the precoating method more effectively diminished the dependence of the relative humidity on the oxygen transmission rate of pure EVOH and increased the oxygen barrier properties of EVOH at a high relative humidity. The incorporation of EFG into EVOH by the precoating method also induced relatively more enhanced thermal stability. These results suggest the feasibility of the application of moisture‐sensitive EVOH resin for food packaging films. POLYM. COMPOS., 37:1744–1753, 2016. © 2014 Society of Plastics Engineers